Aligning public expenditure for agricultural development priorities under rapid transformation: The case of China - Yu, Bingxin; Chen, Kevin Z.; Zhang, Haisen (International Food Policy Research Institute, 2014)
This paper provides a comprehensive review of agricultural policy and public agricultural expenditure (PAE) in China. China shifted away from taxing agriculture to supporting agriculture in the mid-2000s, but the sector faces mounting demographic, biophysical, and trade challenges. PAE in China is outpacing that of other developing economies in Asia, but its composition does not align perfectly with the development challenges and priorities the sector faces.